Genetics and Stability of Resistance to Watermelon Chlorotic Stunt Virus in Melon (Cucumis Melo L). - T. Yousif, Mohamed; A. El Jack, Ali; A. Dafalla, Gasim; Kheyr-Pour, Ahmed; Gronenborne, Brono; Pitrat, Michel; Dogimont, Cathrine (Gezira Journal of Agricultural Science; Vol 3 No 1 (2005), 2021)
Experiments were carried out under field conditions at the University Gezira Research Farm, Sudan and the agroinoculation and green houses conditions in France (le Centre National de la Recherche Scientifique (CNRS*) and le Institut National de la Recherche Agronomique (INRA**) to study the inheritance and stability of resistance to watermelon chlorotic stunt virus (WCSV) in melon ( C. melo L.).   The techniques of autoradiography, using the ratioactive WCSV P 32 , probe was used to detect WCSV in plant tissue and the phospho-imager machine was used to obtain quantified results of DNA particles within the examined plant tissue. The results indicated the presence of one dominant gene and another recessive independent gene controlling WCSV resistance in the resistant lines P1414723, P1124112 and HSD2445- 005. Multi-locational trials on resistant lines under natural field conditions revealed that the resistance to WCSV in melon is uniform and stable. Results of studying the movement of the virus within the plant tissues indicated that the blockage in the plant indigenous trafficking system was one of the mechanisms that are involved in plant resistance to WCSV in the lines P1414723, P1282448, P1124440, Pl 124112, 90625 and HSD 2445-005.